Upaya Peningkatan Kualitas Sekolah melalui Program Kampus Mengajar Angkatan 2 - Reza Rizkynata; Retnowati Wahyuning Dyas Tuti; Izzatusolekha Izzatusolekha (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
Efforts have been made to improve the quality of schools through the class 2 teaching campus program organised by the Ministry of Education and Research and Technology through the Independent Learning Campus policy. The Teaching Campus program has a main mission in the form of increasing the understanding of literacy and numeracy for students in the midst of the Covid-19 pandemic. With the mission carried out by students who are deployed directly to schools in their assignments, it is hoped that it can increase reading interest and interest in learning for Asy-Sarkowi Islamic Elementary School students. In addition to literacy and numeracy, students also participate in assisting schools in adapting technology by providing learning through the AKSI application for elementary schools and assisting school administration management as an effort to improve the quality and quality of the school so that it can make a progressive school for the future. However, before students are sent directly to assignments, students are given briefing in the form of providing material that will later be useful and can help students when they go directly to the assignment location.